Why is China Growing So Fast?. (Economic Issues; Economic Issues ;, 1997)
Since 1978 the Chinese economy has grown on average more than 9 percenta year. Per capita income has nearly quadrupled in the past 15 years andsome analysts predict that within 20 years the Chinese economy will belarger than that of the United States. This pamphlet analyzes the reasonsfor the extraordinary growth of the Chinese economy.